Digital Transformation and Digital Innovation to Improve the Financial Performance of People's Economic Banks (BPR) in Indonesia - Kirowati, Dewi; Kumalawati, Lely; Nauval Prastyanika Putra , Yudha (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
The aim of this research is to determine the extent of digital transformation and digital banking innovation carried out by BPRs in Indonesia to improve financial performance. The type of research used is qualitative research, using descriptive methods and secondary data sources where data collection is obtained by observation and documentation. /literature study that examined data on digital innovation and financial performance of People's Economic Banks (BPR) from 2019 to 2024. The results of the research show that the level of digitization of BPR transaction products or services in Indonesia is still low which has an impact on financial performance, namely a decline in the quality of BPR credit which is quite significant and the BPR Return on Assets (ROA) ratio continues to show a significant decline. Under these conditions, BPR's financial performance is still in a positive or maintained condition. Steps that must be taken by BPR can be to carry out analyzes related to customer needs and values, evaluate product and service development capabilities in accordance with BPR business strategy, and design development including developing IT infrastructure, quantity and quality of human resources, capital, and collaboration and cooperation with conventional banks. , Government, and the business/industrial world and other institutions in a sustainable manner